Metal additive manufacturing: Technology, metallurgy and modelling - Cooke, Shaun; Ahmadi, Keivan; Willerth, Stephanie; Herring, Rodney (Journal of manufacturing processes, 2020)
This paper provides a comprehensive review of metal additive manufacturing, a rapidly evolving field with innovative technologies and processes. The purpose of this review paper is to provide a complete picture of the current research on metal AM and its capabilities. An overview of metal AM and the current processing methods are provided, along with a brief introduction to the complex physics behind the melt pool formation. Common metal AM characteristic defects are discussed as well as the current metals and alloys that are commercially available. Furthermore, process optimization techniques and computational modelling methods are reviewed. Lastly, various post-processing methods to improve surface roughness, mechanical properties and dimensional precision are discussed. Although the library for printable alloys is increasing, there is still a need for alloy development outside of the commercial setting. Furthermore, there is currently not a complete numerical model of the AM process which is mainly due to the computational costs. Although metal AM is still in its infancy, the frequency and significance of new developments are driving AM to mainstream adoption.